Analysis Of Constrains In The Use of IT-Based Learning Media In Elementary School - Niska Ramadani; Hanafa Putri Ferfinal; Ferdinal. R (Indonesian Journal of Computer Science and Engineering, 2025)
This study aims to analyze the constraints in implementing IT-based learning media in elementary schools. The rapid advancement of technology demands the integration of Information Technology (IT) into education; however, many educational institutions still face various obstacles. The research method used was a Systematic Literature Review (SLR). A total of 35 relevant scientific articles were collected, categorized, and analyzed. Data collection focused on the keywords IT-based learning media, digital learning challenges, and elementary school. The results of the study indicate two main constraints in implementing IT-based learning media in elementary schools: the lack of teachers’ competence in using technology and limited technological facilities, especially in rural schools. The implication of these findings is that the successful integration of IT-based learning media in elementary education requires a holistic intervention. Such intervention includes continuous professional development for teachers and the establishment of supportive school policies to ensure the effective integration of technology in elementary education.